Influence of diameter on mechanical behavior of morse taper narrow implants - Reis, Tais Alves dos (2022)
Dental implants could give back function, esthetics and quality of life to patients. The correct choice of the implant, especially in borderline cases, is essential for a satisfactory result. Aim: Thus, the objective of this study was to evaluate the mechanical behavior of Morse taper implants with two different prosthetic interfaces. Methods: Twenty self-locking Morse taper implants, 2.9 mm in diameter (FAC), and 20 Morse taper implants, 3.5 mm in diameter (CM) were divided into two groups (n=10), and submitted to strength to failure test, optical microscopic evaluation of fracture, metallographic analysis of the alloy, finite element analysis (FEA) and strain gauge test. A Student’s t test (α = 0.05) was made for a statistical analysis. Results: For the strength to failure test, a statistically difference was observed (p <0.001) between FAC (225.0 ± 19.8 N) and CM (397.3 ± 12.5 N). The optical microscopic evaluation demonstrated a fracture pattern that corroborated with FEA´s results. The metallographic analysis determined that the implants of the FAC group have titanium-aluminum-vanadium alloy in their composition. In the strain gauge test, there was no statistical difference (p = 0.833) between CM (1064.8 ± 575.04 μS) and FAC (1002.2 ± 657.6 μS) groups. Conclusion: Based on the results obtained in this study, ultra-narrow implants (FAC) should ideally be restricted to areas with low masticatory effort.